Heavy metal contamination and potential health risks in upland rice-producing soils of rotational shifting cultivation in northern Thailand - Noppol Arunrat; Praeploy Kongsurakan; Sukanya Sereenonchai (Environmental Sciences Europe)
Abstract Rotational shifting cultivation (RSC) is commonly practiced in northern Thailand for upland rice cultivation, primarily for household consumption. However, the potential health risks from heavy metal contamination in these soils have not been thoroughly explored. This study aimed to evaluate the contamination of six heavy metals (Arsenic (As), Mercury (Hg), Cadmium (Cd), Lead (Pb), Copper (Cu), and Chromium (Cr)) in upland rice across RSC fields with varying fallow periods and assess the associated health risks from rice consumption. Four RSC fields with 5, 6, 10, and 12-year fallow periods were examined. The RSC-6Y and RSC-12Y fields were used for upland rice cultivation in 2022, while the RSC-5Y and RSC-10Y fields were cultivated in 2023. The geo-accumulation index (Igeo) was calculated, and translocation factors (TF) were assessed for the transfer of heavy metals from soil to straw (TFStraw/Soil), straw to grain (TFGrain/Straw), and soil to grain (TFGrain/Soil). The results indicated that after burning vegetation in the RSC fields, the highest concentrations of Pb, Cr, and Hg were found in the ash. In RSC soils, Cu, Cr, As, Pb, and Hg levels were below reference standards, with Cd undetected. In rice grains, the order of concentration was Pb > Cu > Cr > As, with Hg and Cd undetected. Pb levels in rice grains exceeded the safety threshold. Igeo values indicated no contamination to moderate contamination across sites, with negative Igeo values for Cr and Cu, and zero values for Cd. The TF results showed limited transfer of As, Hg, and Cd from soil to rice plants (TFStraw/Soil < 0.1), but notable transfer for Pb, Cr, and Cu. Pb was readily transferred from soil to grain (TFGrain/Soil), posing a potential health risk. The study highlights potential non-carcinogenic and carcinogenic risks from heavy metal exposure, particularly Pb, and underscores the need for further research to determine contamination sources and mitigation strategies.